An automated data acquisition system for pinch grip assessment based on Fugl Meyer protocol: a feasibility study - Alsayed, Abdallah S. Z.; Raja Ahmad, Raja Mohd Kamil; Harun @ Ramli, Hafiz Rashidi; As'arry, Azizan (MDPI, 2020)
The Upper Extremity Fugl Meyer Assessment (UE-FMA) is the most comprehensive assessment for pinch impairment after stroke. The pinch test of UE-FMA is manually performed by pulling a pincer object away from the patient’s fingers while providing a visual observation that results in a subjective assessment. In this study, an automated data acquisition system that consists of a linear electric actuator applying automatic pulling to the customized pincer object held by the volunteer was developed. The pinch force was measured such that a strain gauge was placed on the pincer object while pulling force was measured using pulling force load cell connected in between the linear electric actuator and customized pincer object. The pincer object’s slip onset was detected using a displacement slip sensor. The mean pinch and pulling force values at the slip onset were 12.17 and 6.25 N for right hands, while mean pinch and pulling force values were 11.67 and 5.92 N for left hands of 50 healthy volunteers, respectively. Based on the paired t-test, there is no significant difference between right and left hands. The automated data acquisition system can objectively apply a pulling force, detect the slip onset, and measure the pinch and pulling forces.